Experiences of the graduates of the first baccalaureate midwifery programme in Pakistan: A descriptive exploratory study. (April 2018) - Lakhani, Arusa; Jan, Rafat; Baig, Marina; Mubeen, Kiran; Ali, Sadia Abbas; Shahid, Shahnaz; Kaufman, Karyn
Abstract: Background: in 2012 the Aga Khan University in Karachi, Pakistan opened the country's first bachelor's degree program in midwifery for women who held diplomas in nursing and midwifery. The principal aims were to prepare midwives who would be competent to provide full-scope practice. For quality assurance, the programme was continuously monitored and assessed. As part of this ongoing evaluation process we sought in-depth feedback from the first graduates about their student experiences. Objective: this study aimed to explore the experiences of the first graduates of a Bachelor of Science in Midwifery (BScM) program to deepen our understanding of their views of the program's strengths and difficulties and to obtain their suggestions for change. Design and Methods: This qualitative descriptive exploratory study used universal sampling to collect data from all 21 of the first graduates of the BScM Program. Data collection involved focus group discussions using a semi structured interview guide and content analysis. The study was approved by Institutional Ethics Review Committee. Findings: three main themes emerged from the data: (1) Competence acquisition, (2) Attitude transformation, and (3) Strengths and limitations of the program. Conclusions: the study findings highlighted that the degree program in midwifery had a positive impact on graduates' perceptions of their knowledge, skills, attitudes and ability to implement evidence-based midwifery practice. The graduates regarded the university's environment, teaching-learning strategies, preceptorship model, self-directed learning and exposure to diverse clinical settings as major facilitators in achieving competence.